Depiction of non-Muslims in the secondary Islamic studies syllabus and its impact on Muslim students’ level of religious tolerance: IISM as a case study - Ramdane, Tahraoui; Souad, Merah (2019)
Private and government sector schools in most Muslim countries make Islamic studies a compulsory subject for all Muslim students up to the Secondary school level. Mandatory use of Islamic Studies textbooks in Islamic schools makes them a powerful tool that forms emotions, ideas, and perceptions. They often guide students to generate strong spiritual connections with their religion that can be empowered to various ends. It is through the primary, elementary, and secondary Islamic textbooks that main traits, norms, values, behaviors, and convictions of Muslim pupils’ personality are built. In addition, most schools policies declare that the main aim of Islamic Education training is to enable their students to lead their lives according to the teachings of the Qur'an and Sunnah so that they grow up as true practicing Muslims. Furthermore, cultures and religions of others also occupy a decent space in the discourse of the primary, elementary and secondary Islamic syllabus. In theory, Islamic curriculum promotes mutual respect, harmony and cooperation with other religions – heavenly in particular. In practice, however, intolerant and negative images of the religious “other” are often presented through the interpretation of Islamic holy texts by Islamic studies teachers. Using a qualitative approach, this research aims at investigating the close relationship between the Islamic conceptualization of curriculum and the nature of the Islamic faith, the items of learning and skills which an Islamic academic program offers to learners therein in order to enable them to attain the degree of perfection for which Allah has prepared for them. It also aims to highlight the Islamic traditional morality and the conventional depiction of non- Muslims in the Islamic Studies rhetoric and its influence in shaping stereotypes on the “Other”. For that, the extent of impact that Islamic textbooks and syllabus possess in creating tolerant or intolerant trends among Muslim students through the depiction of the “Other” were analyzed in order to explain the role of Islamic Studies syllabus in shaping Muslim students’ views towards themselves and towards Others (non-Muslims and nonSunni). It is expected that the results of this study will help in clarifying the need of more efforts to revive the Islamic curriculum, and address the issues of rigidity, passivity, irrelevancy and social alienation which continue to plague the Islamic curriculum. Besides It is expected that the results of this study will help in clarifying the need for a language of tolerance and moderation to be adopted in addressing the Other (non-Muslims and non-Sunni) via education in general and the Islamic Studies textbooks in general, in order to reduce the gap between religions and sects, and to prepare young Muslims living and working in harmony with humanity at large.